DAMPAK TEKNOLOGI PENDIDIKAN TERHADAP PENILAIAN AFEKTIF SISWA - Unik Hanifah Salsabila; Dimas Aprisal Susetyo; Fauzan Firdaus; Abdul Muis Al Fikri; Muhamad Aldo Al Fikri (Sekolah Tinggi Pariwisata Mataram, 2021)
When technology enters the realm of education, all its sub-sectors will experience an impact that is felt both on a small and large scale. The impact on the assessment process is inevitably negative and positive. Affective Assessment is still a hot topic of conversation and the obstacles have yet to be resolved. This makes it an obstacle because technology is involved in matters of affective assessment aspects in the world of education. The purpose of this article is to discuss the problems experienced by teachers in general regarding the above obstacles, namely technology and affective assessment. The author explains how the teachers in the affective assessment process through the use of technology and so on. Articles are made through literature review research by collecting library sources related to the scope of discussion about technology, education and assessment. The article produces a solution that has been offered to solve the problems that have become obstacles for teachers in the world of education in the technology era. With the impact that occurs from technology on affective assessment, it results in problems that need to be solved with the solutions given and can be used as a basis for the future so that education can be better.